Archaeology and Buddhism in South Asia, 1st edition - Ray, Himanshu Prabha (Routledge, 2020)
This book traces the archaeological trajectory of the expansion of Buddhism and its regional variations in South Asia. Focusing on the multireligious context of the subcontinent in the first millennium BCE, the volume breaks from conventional studies that pose Buddhism as a counter to the Vedic tradition to understanding the religion more integrally in terms of dhamma (teachings of the Buddha), dāna (practice of cultivating generosity)and the engagement with the written word. The work underlines that relic and image worship were important features in the spread of Buddhism in the region and were instrumental in bringing the monastics and the laity together. Further, the author examines the significance of the histories of monastic complexes (viharas, stupas, caityas) and also religious travel and pilgrimage that provided connections across the subcontinent and the seas.